A crab claw shaped molecular receptor for selective recognition of picric acid: supramolecular self-assembly mediated aggregation induced emission and color change. Issue 26 (19th June 2017) - Pitchaimani, Jayaraman; Kundu, Anu; Karthikeyan, Subramanian; Anthony, Savarimuthu Philip; Moon, Dohyun; Madhu, Vedichi
Abstract : A crab claw shaped neutral molecular receptor selectively recognize picric acid. Abstract : 2, 6-Pyridine bis(iminoantipyrine) (PyBAP), a crab claw shaped open neutral molecular receptor with multiple non-covalent sites, showed selective recognition of picric acid (PA) through supramolecular interactions that lead to an intermolecular charge transfer induced naked-eye detectable color change both in solution as well as in the solid state and rare turn-on solid state fluorescence. The selective host–guest formation of PyBAP–PA has been confirmed using 1 H-NMR, single crystal structural analysis and computational studies.